Research trends of creative thinking skill in science education journals in Indonesia: Design analysis and data analysis techniques - Pratama, Ferry Yudha; Mahardiani, Lina; Bramastia, Bramastia (Journal of Environment and Sustainability Education, 2025)
Creative thinking as one of the 21st skills is not only beneficial but also essential, particularly in learning sciences. Creative thinking equips them with the cognitive flexibility to devise innovative solutions, consider multiple variables, and approach challenges from diverse angles, fosters critical reasoning and imagination, and enhances student motivation and engagement within science classrooms. This paper will focus on investigating the implementation of creative thinking in learning sciences based on the articles published in national accreditation journals in Indonesia. The content analysis approach was applied, leveraging the method of scanning published research journal documents as its research method. This study is distinctive from previous research on creative thinking skills in several ways covered on all educational articles published from 2015 to 2024 in all Indonesian science education journals. This study revealed that in the last three years, the number of publications focusing on creative thinking skills has increased. The most dominant research is quantitative research with quasi experiment as the research design. Meanwhile, junior high school students, and 'biology' with the subject material of 'environmental pollution' were consecutively the subjects, science fields of study, and topics most chosen by researchers. Project Based Learning (PjBL), test sheet, and N-gain were the most frequently used as treatments, instruments, and data analysis methods, respectively. The review highlights the need to increase the use of qualitative and mixed-method approaches, explore the integration of local wisdom and ethnoscience through R&D, and focus on developing instructional products to enhance students’ low creative thinking abilities. Additionally, researchers are advised to clearly report their research instruments, including validity and reliability, and to select data analysis techniques that align with their research objectives and design.